Creative-Self of Teachers in Utilizing Applications for Online English Learning during the COVID-19 Pandemic - Fajar Nurkhana; Arief Eko Priyo Atmojo (Ahmad Dahlan Journal of English Studies, 2021)
The COVID-19 pandemic has hit all over the world and had a significant impact on various aspects of life. Education is one aspect affected by the pandemic. Teachers are challenged to use online learning applications for the optimal learning process like face-to-face learning. It takes creativity to adapt and create optimal results during a pandemic. This study aimed to find out teachers’ creative-self dynamics and interpretation in utilizing applications for online English learning during the COVID-19 pandemic. This study used a qualitative method with a phenomenological approach. Sampling was carried out by purposive sampling method with interviews and observations. The samples or subjects were 2 English Teachers of Public Vocational School and 2 English Teachers of Private Vocational School aged between 30-50 years, male and female, and had at least WhatsApp. Based on the results, teachers teaching during a pandemic are willing to accept progress, develop, integrate, and use new ways, create new things, understand situations, and seek from various sources of information to make something interactive. The dynamics that arise based on thoughts that give birth to distinctive behavior and impact on individual feelings, are then controlled in a dynamic in new conditions, accompanied by distinctive positive humor that requires harmony in how it works. This study will provide an overview for teachers to understand creative-self to develop a new creation.